Analisis Pengaruh Kualitas Produk, Promosi, dan Citra Merek terhadap Keputusan Pembelian Konsumen pada Brand Skintific - Esilia Puspitasari; Zaenia Vi L. Syuro; Nuha Nur Awaluh; Pupung Purnamasari (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the influence of product quality, promotion, and brand image on consumer purchasing decisions on the Skintific brand. In the competitive skincare industry, these factors play an important role in shaping consumer perceptions and influencing purchasing decisions. The research method used is quantitative with a survey approach, where questionnaires are distributed to consumers of Skintific products. The collected data were analyzed using multiple linear regression to identify the influence of each variable. The results showed that product quality has a positive and significant influence on purchasing decisions, followed by effective promotion and strong brand image. These findings indicate that improving product quality, appropriate promotional strategies, and strengthening brand image can improve consumer purchasing decisions. This study provides insight for Skintific management in formulating more effective marketing strategies to attract and retain customers. The abstract above includes the objectives of the study, the methods used, and the results obtained, in accordance with the academic journal format.